Konsep perbankan Syari’ah - Putri, Rosyadah Rensy Dwi Murnisa (Maliki Interdisciplinary Journal, 2024)
Everything related to Islamic Banks and Islamic Business Units, including their place of business, business activities, and the procedures and methods used to carry out these business activities, is called Islamic Banking. Islamic banks are institutions that act as intermediaries and providers of financial services, which operate based on Islamic ethics and value systems, especially those free from interest (riba). This study aims to find out and understand more deeply about the concept of Islamic banking. This research method uses scientific review articles to understand the concept of Islamic banking and applies a theoretical approach in evaluating the journal's contribution to current theory. The conclusion obtained in this study is that Islamic banks are financial institutions that operate based on Islamic principles and value systems, without interest, and are established to address social and economic problems. The interest system is considered unfair and difficult for farmers and small businesses, so Islamic banks evaluate business plans based on Islamic welfare and justice criteria. Positive law and Islamic law are the basis for Islamic banking in Indonesia. The principles include contract law, independence from the Maghrib, and prudence and trust in financial operations.